Peran vitamin B6 terhadap inflamasi pada adhesi peritoneal pasca laparotomi: tinjauan pustaka - Made Agus Dwianthara Sueta; I Dewa Made Sukrama (DiscoverSys Inc., 2021)
Vitamin B6 or pyridoxine has been shown to modulate hypoxia and inflammation, but it has not yet confirmed their local effects on the peritoneum. Although there was no study regarding this issue, pyridoxine effects on suppressing these two pathways look promising as a preventing agent against peritoneal adhesion. The development of intraperitoneal adhesion post-operation is one of the most common complications after abdominal surgery. Approximately 95% of patients who underwent laparotomy can develop adhesions in the future. Pathogenesis of adhesion consists of three important processes which were induced by trauma: trauma or direct tissue injury-induced suppression of degradation of fibrinolytic matrix and extracellular system, inflammation response with cytokine production, particularly TGF-? and interleukin, also tissue hypoxia as the impact from circulation disorder toward mesothelial cell and sub-mesothelial fibroblasts, which results as increasing hypoxia-inducible factor-alpha (HIF-1?) and vascular endothelial growth factor (VEGF), which are responsible for generating collagen and angiogenesis process. Pyridoxine has biological activity and interesting characteristics in avoiding intra-peritoneal adhesion by dealing with inflammation effects and hypoxia. From the inflammation process, pyridoxine has been shown can hinder macrophage, decrease IL-6, suppress TLR-mediated TAK1 phosphorylation, JNK, IKK-I?B?, which can cause a reduction in NF-?B activation and NLRP3-mediated caspase-1, also suppress iNOS and cyclooxygenase-2 (COX2), which contributed to developing intra-peritoneal adhesion. Vitamin B6 (Vit B6), atau piridoksin telah ditunjukkan dapat memodulasi efek hipoksia dan inflamasi, tetapi belum dikonfirmasi efek lokalnya pada peritoneum. Walaupun belum ada penelitian langsung, efek supresi vitamin B6 terhadap kedua jalur tersebut sangat menjanjikan sebagai agen prevensi adhesi peritoneal. Perkembangan adhesi intraperitoneal pasca operasi adalah salah satu komplikasi paling umum setelah operasi abdominal. Sekitar 95% pasien yang menjalani laparotomi akan mengalami perlengketan di kemudian hari. Patogenesis adhesi melibatkan tiga proses penting yang diinduksi trauma: trauma atau kerusakan jaringan langsung menginduksi penghambatan sistem degradasi matriks fibrinolitik dan ekstraseluler, respons inflamasi dengan produksi sitokin, terutama TGF-? dan interleukin, serta hipoksia jaringan sebagai akibat dari gangguan suplai darah ke sel mesothelial dan fibroblas submesothelial, yang mengarah pada peningkatan hypoxia inducible factor-alpha (HIF-1?) dan faktor pertumbuhan endotel vaskular (VEGF), yang bertanggung jawab untuk pembentukan kolagen dan angiogenesis. Vitamin B6 menyajikan sifat dan aktivitas biologis yang menarik untuk mencegah adhesi intraperitoneal dengan mengatasi efek inflamasi dan hipoksia. Pada jalur inflamasi, vitamin B6 terbukti menghambat makrofag, menurunkan IL-6, menghambat fosforilasi TLR-mediated TAK1, JNK, serta IKK-I?B?, yang menyebabkan penurunan aktivasi NF-?B and NLRP3-mediated caspase-1, serta menghambat iNOS dan cyclooxygenase-2 (COX2) yang berkontribusi terhadap pembentukkan adhesi intraperitoneal.